DEVELOPMENT MODEL MANAGEMENT EDUCATION SOFT SKILL NURSES HOSPITAL EDUCATION - Mardliyah Mardliyah (Universitas Muhammadiyah Semarang, 2018)
This research intent for management model development education soft skill nurse at education hospital, and has influence increase nurse’s soft skill on nurses unit. This modeldevelopment utilize method with approaching Research & Development from Borg & Gall(2007). Since time and cost limitation therefore is utilized a portion step of 10 Borg's stepsand Gall, which is: (1 ) research & information as introduction step foreword, (2 ) planing &develop preliminary form of product as step of makings designs start model, (3) preliminaryfield testing & revision as step of early model checking, (4 ) main field testing & revision asstep of product feasibility test-driving and product revision, (5) analize and studies toestablish final products (final product), and (6) disemination. Managements modeldevelopment education soft skill nurse at indispensable Education Hospital whereas nursecandidate or nurse college’s students that of its upstream of nurse service, and nursecandidate constitutes one of primal component in education management process in meets theneed development soft skill nurse, therefore management model development education softskill indispensable nurse, so is expected that can also minimalize complain of customer